Toxicity of Bacillus thuringiensis at different larval ages of Agrotis ipsilon (Lepidoptera: Noctuidae) - Kaiser, Ingrid Schimidt; Lima, Victor Luiz Souza; Pratissoli, Dirceu; Machado, Lorena Contarini; Bueno, Regiane Cristina Oliveira de Freitas (Revista de Ciências Agroveterinárias, 2020)
The black cutworm Agrotis ipsilon (Hufnagel) (Lepidoptera: Noctuidae) is a cosmopolitan and polyphagous pest that attacks diverse crops and weed. One of the alternatives to insecticides may be the use of bioinsecticides based on Bacillus thuringiensis Berliner (Bt). Thus, the objective of the present study were evaluating the toxicity of Agree® and Dipel® bioinsecticides based on Bt on different larval ages of A. ipsilon. For the experiments, five larval ages were used (0-24, 48-72, 96-120, 144-168, and 192-216 h). The A. ipsilon caterpillars were individualized in acrylic tubes containing an artificial diet and 50 μL of each biopesticide in the concentration 1 × 108 spores mL-1. Mortality was assessed for seven days. The two bioinsecticides evaluated promoted mortality at all larval ages of A. ipsilon. The age of 0-24 h had mortality above 90%. The values of LC50 and LC90 were 9.8 × 105 and 7.4 × 106 spores mL-1 for Agree® and 1.3 × 106 e 1.4 × 107 spores mL-1 for Dipel®, respectively, without difference between LC50 and LC90 values of the bioinsecticides. The results indicate that younger caterpillars are more susceptible to Bt-based bioinsecticides.